2002
DOI: 10.1111/j.1346-8138.2002.tb00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Cutaneous Mastocytosis: Pseudoxanthomatous Variant

Abstract: Diffuse cutaneous mastocytosis is one of the extremely rare benign forms of mastocytosis that have varied clinical presentations. The pseudoxanthomatous variant is an extremely rare multinodular nonpigmented entity. Only two cases have been reported so far in the literature. We report a 21 year old female patient who had diffusely infiltrated skin with multiple papulo‐nodular lesions resembling xanthomas and the classical histopathological features of mastocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Moreover, we observed that the skin symptoms appeared in age‐dependent manner. Extensive bullous lesions predominated in infancy, whereas diffuse infiltration of the skin developed further in the course of the disease as it has been previously reported 9,17 …”
Section: Discussionsupporting
confidence: 58%
“…Moreover, we observed that the skin symptoms appeared in age‐dependent manner. Extensive bullous lesions predominated in infancy, whereas diffuse infiltration of the skin developed further in the course of the disease as it has been previously reported 9,17 …”
Section: Discussionsupporting
confidence: 58%
“…Childhood disease may resolve spontaneously. With advancing age, there is risk of extracutaneous involvement and of development of malignancies 5 . Although upon treatment, itching and lesions have shown improvement in this case, the disease may persist or even worsen and therefore long‐term prognosis remains guarded.…”
Section: Discussionmentioning
confidence: 84%
“…This multinodular nonpigmented variety of mastocytosis is extremely rare. In this variety, as against a classic Darier's sign, only erythema without urtication is elicited by rubbing 5 . Skin biopsy reveals dense dermal infiltrate of mast cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study on 17 mastocytomas, a pseudoxanthomatous aspect has been reported in up to 40% of cases [6] . In the pseudoxanthomatous variant of diffuse cutaneous mastocytosis there are numerous yellowish pap-ules or nodules associated with the other cutaneous signs [8] . Histologically, in pseudoxanthomatous forms, there is a typical dense mast cell infi ltrate in the deep dermis that might explain the yellow colour of the lesions [9] .…”
Section: Discussionmentioning
confidence: 99%